ISOLASI JAMUR ENDOFIT AKAR KEDELAI DAN UJI PENGHAMBATANNYA TERHADAP FUSARIUM OXYSPORUM SEBAGAI AGEN PENGENDALI HAYATI - Yuni, Sri Wahyuni Wahyuni; Ani, Nomi Noviani Novi (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2019)
Endophytes are microbes (bacteria, fungi, or actinomycetes) that live and colonize the host tissue without causing negative effects, even giving benefits to the host. One of the advantages is as a biological control agent for both insect pests and pathogens that cause plant diseases. As a biological agent, endophytes can reduce plant damage by insects, nematodes, or pathogens that cause disease through induction of plant resistance. In addition, endophytes can also function as biological agents through antagonistic interactions and competition. The purpose of this study was to obtain endophytic fungi which are potentially as biological agents of insect pests; the mechanism, as well as the application of endophytes in plantation crops. The potential of enndofit fungus in controlling Fusarium sp carried by soybean seeds was also tested.